Effect of epidural block on surgical conditions during pediatric subumbilical laparoscopic surgery involving a supraglottic airway: a randomized clinical trial - Wu, Lei; Wei, Siwei; Xiang, Zhen; Yu, Eryou; Chen, Zheng; Du, Zhen; Qu, Shuang Quan (Frontiers in Medicine, 2023)
Background: Few studies have examined the effect of epidural block on surgical conditions during pediatric subumbilical laparoscopic surgery involving a supraglottic airway (SGA). This study investigated the surgical condition scores for such procedures in cases where neuromuscular block, epidural block, or neither was used.Methods: A total of 150 patients aged 3-12 years undergoing laparoscopic orchiopexy with a ProSeal SGA device laryngeal mask airway were randomly allocated to one of three groups: the control group (did not receive neuromuscular block and epidural block), the NMB group [received a neuromuscular block (train-of-four 1-2 twitches) using rocuronium], or the EDB group (received an epidural block using ropivacaine). The primary outcome was the quality of surgical conditions evaluated with the Leiden-Surgical Rating Scale by the blinded surgeon. The secondary outcome measures included intraoperative hemodynamic data (including mean arterial pressure and heart rate), the SGA device laryngeal mask removal time, the PACU discharge time, the pain score in the PACU and intraoperative adverse events (including bradycardia, hypotension, peak airway pressure Ppeak>20 cmH2O, and poor or extremely poor surgical conditions occurred during the operation). Statistical analysis was performed with one-way analysis of variance, the Kruskal-Wallis test, the chisquare test or Fisher's exact test. Bonferroni corrections for multiple comparisons were made for primary and secondary outcomes.Results: Surgical condition scores were significantly higher in the NMB and EDB groups than in the control group (median difference: 0.8; 95% confidence interval [CI], 0.5-1.0; P<0.0001; and median difference: 0.7; 95% CI, 0.5-0.8; P<0.0001, respectively). Blood pressure and heart rate were significantly lower in the EDB group than in the other two groups (P<0.0001 and P=0.004). Patients in the EDB group had significantly lower pain scores during PACU than those in the other two groups (P<0.0001). The sufentanil dose was lower in the EDB group than in the other two groups (P=0.001).Epidural block can improve surgical conditions during pediatric subumbilical laparoscopic surgery involving a SGA supraglottic airway to a degree comparable to that with moderate neuromuscular block.